Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Sabun Dettol Di Mini Market El-Jhon Sawah Lebar - Eki Indrajaya; Ermy Wijaya; Yudi Irawan Abi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of product quality and promotion on purchasing decisions for Dettol soap at the El-John Sawah Lebar Mini Market. The sample in this study was 80 consumers who purchased Dettol soap at the El-John Sawah Lebar Mini Market. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed Y = 9.200 + 0.308X1 + 0.480 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (product quality) and X2 (promotion) on the purchasing decision of Dettol soap (Y). Means that if product quality and promotion variables increase, it will increase purchasing decisions. The magnitude of the coefficient of determination is 0.501. This means that X1 (product quality) and X2 (promotion) affect the purchasing decision (Y) of Detootl soap at the El John Sawah Lebar Mini Market by 50.1% while the remaining 49.9% is influenced by other variables not examined. in this research. The results of the t test at a significance level of 0.05 explained that partially the product quality and promotion variables had a significant influence on the Dettol soap purchasing decision variable at the El-John Sawah Lebar Mini Market. The result of the F test at a significance level of 0.05 explains that the product quality and promotion variables have a simultaneous (together) influence on the decision to purchase Dettol soap at the El-John Sawah Lebar Mini Market.